Leading through polycrisis: leadership capital and institutional development under Prime Minister Masrour Barzani in the Kurdistan Region of Iraq - Ehsan Shareef Salih (International Journal of Public Leadership, 2026)
Purpose Public leadership scholarship has paid limited attention to how leaders operate under persistent polycrisis, where crisis is structural rather than episodic. This article examines how Prime Minister Masrour Barzani's Ninth Cabinet (2019–2025) in the Kurdistan Region of Iraq deployed political leadership to convert overlapping crises into pathways for institutional development. It positions leadership – not crisis severity or institutional structure – as the central explanatory factor shaping governance outcomes under constraint. Design/methodology/approach The study adopts a theory-informed qualitative case study using process tracing and triangulated documentary analysis. Evidence is drawn from official records, budgetary data, parliamentary materials, and independent and critical sources. The analysis evaluates rival explanations – symbolic signalling, short-term containment and institutional capacity expansion – to assess the depth and durability of change. Findings The article develops the concept of Leadership-Mediated Crisis-Induced Developmental Governance (LCIDG), showing how leadership capital – skills, relational authority and reputation – mediates the relationship between polycrisis and institutional outcomes. Four mechanisms are identified: window activation, constraint-induced innovation, institutional layering and implementation-driven consolidation. Findings indicate that crisis does not automatically generate reform; leadership determines whether it reinforces fragmentation or enables incremental capacity formation. Originality/value This article contributes to public leadership theory by demonstrating that leadership capital functions not only as a political resource but as a mechanism for institutional transformation under crisis conditions. It extends leadership scholarship into fragile, subnational contexts and reframes polycrisis as a conditional arena for leadership-driven development rather than solely a source of governance breakdown. The study provides a mechanism-based framework applicable to leaders operating under structural constraint in comparable governance environments.